Gamified Vocabulary Learning as a Pathway to Realizing the Human Right to Education for Vocational Students (Contrarius Series: Law & Social Justice, 2026)
This review explores how gamified, checkpoint-based vocabulary learning supports the human right to education by promoting inclusive, equitable, and high-quality English instruction within Technical and Vocational Education and Training (TVET) contexts. Drawing from empirical and theoretical sources, the paper discusses gamification as an instructional innovation that aligns with human rights principles of participation, autonomy, and empowerment. Checkpoint-based designs, such as the dual structure of digital recall and peer interaction, offer meaningful opportunities for learners to experience linguistic growth through accessible and engaging modalities. By integrating game-based digital tools with collaborative activities, educators not only enhance vocabulary retention and speaking confidence but also advance social justice in education through learner inclusion. This review advocates embedding gamified checkpoints into vocational English curricula as a pedagogical expression of the right to education for all learners, particularly those marginalized by conventional academic structures.